Contingency Contracting Untuk Menurunkan Perilaku Tertidur Di Kelas Pada Anak Sleep Disorder - Mahardhika, Nadia Felicia; Pudjiati, Sri Redatin Retno (Persona:Jurnal Psikologi Indonesia, 2019)
AbstractNormal sleep patterns are very important for academic achievement and life of each child. This study aims to know the effect of Contingency Contracting to reduce sleep behavior in class and improve sleep patterns in children with Circadian-Rhythm Sleep Disorder. The study subjects were A, a boy aged 11 years, with ADHD-PI diagnosed with Circadian-Rhythm Sleep Disorder Delayed Sleep Phase Type. The design of this study uses multiple-baseline-across-behaviors design. Contingency contracting interventions are carried out using prompt techniques, fading, and economic tokens. The recording instrument used is sleep diary and behavior frequency recording sheet. The results of the study show that behavioral modification intervention programs carried out with contingency contracting have been shown to effectively reduce sleep behavor in the classroom in the morning and improve the pattern of nighttime sleep in children with Circadian-Rhythm Sleep Disorder.Keywords: sleep-disorder; circadian-rhythm; behavior modification; contingency contracting; prompt  AbstrakPola tidur yang normal sangatlah penting bagi prestasi akademik dan kehidupan setiap anak. Penelitian ini bertujuan melihat pengaruh Contingency Contracting untuk menurunkan perilaku tertidur di kelas dan memperbaiki pola waktu tidur pada anak dengan Circadian-Rhythm Sleep Disorder. Subjek penelitian adalah A, anak laki-laki usia 11 tahun, dengan ADHD-PI didiagnosa mengalami Circadian-Rhythm Sleep Disorder Delayed Sleep Phase Type. Desain penelitian ini menggunakan multiple-baseline-across-behaviors design. Intervensi contingency contracting dilakukan menggunakan teknik prompt, fading, dan token ekonomi. Instrumen pencatatan yang digunakan adalah sleep diary dan lembar pencatatan frekuensi perilaku. Hasil dari penelitian menunjukkan program intervensi modifikasi perilaku yang dilakukan dengan contingency contracting terbukti efektif menurunkan perilaku tertidur di kelas pada pagi hari maupun memperbaiki pola waktu tidur malam hari pada anak dengan Circadian-Rhythm Sleep Disorder.Kata Kunci: sleep-disorder; circadian-rhythm; modifikasi perilaku; contingency contracting; prompt